Gene expression profiling reveals insights into infant immunological and febrile responses to group B meningococcal vaccine. Issue 11 (19th November 2020) - O'Connor, Daniel; Pinto, Marta Valente; Sheerin, Dylan; Tomic, Adriana; Drury, Ruth E; Channon‐Wells, Samuel; Galal, Ushma; Dold, Christina; Robinson, Hannah; Kerridge, Simon; Plested, Emma; Hughes, Harri; et al.
Abstract: Neisseria meningitidis is a major cause of meningitis and septicaemia. A MenB vaccine (4CMenB) was licensed by the European Medicines Agency in January 2013. Here we describe the blood transcriptome and proteome following infant immunisations with or without concomitant 4CMenB, to gain insight into the molecular mechanisms underlying post‐vaccination reactogenicity and immunogenicity. Infants were randomised to receive control immunisations (PCV13 and DTaP‐IPV‐Hib) with or without 4CMenB at 2 and 4 months of age. Blood gene expression and plasma proteins were measured prior to, then 4 h, 24 h, 3 days or 7 days post‐vaccination. 4CMenB vaccination was associated with increased expression of ENTPD7 and increased concentrations of 4 plasma proteins: CRP, G‐CSF, IL‐1RA and IL‐6. Post‐vaccination fever was associated with increased expression of SELL, involved in neutrophil recruitment. A murine model dissecting the vaccine components found the concomitant regimen to be associated with increased gene perturbation compared with 4CMenB vaccine alone with enhancement of pathways such as interleukin‐3, ‐5 and GM‐CSF signalling. Finally, we present transcriptomic profiles predictive of immunological and febrile responses following 4CMenB vaccine. SYNOPSIS: A randomised clinical trial evaluates transcriptomic and proteomic profiles following infant concomitant 4CMenB vaccination, compared with control vaccines alone. A novel framework is provided for both understanding and predicting vaccine immunogenicity and reactogenicity. 4CMenB vaccination is associated with a distinct gene expression and plasma protein signature. Post‐vaccination fever is associated with increased expression of SELL, involved in neutrophil recruitment. Transcriptomic profiles predictive of immunological and febrile responses following 4CMenB vaccine are presented. Abstract : A randomised clinical trial evaluates transcriptomic and proteomic profiles following infant concomitant 4CMenB vaccination, compared with control vaccines alone. A novel framework is provided for both understanding and predicting vaccine immunogenicity and reactogenicity.